Supercapacitance/Resistance Behaviors of Helminth Eggs as Reliable Recognition and Direct Differentiation Probe - Shaali, Ruhollah; Doroodmand, Mohammad Mahdi; Moazeni, Mohammad (Frontiers in Bioengineering and Biotechnology, 2021)
Parasitic helminths are usually known as undesired pathogens, causing various diseases in both human and animal species. In this study, we explore supercapacitance/ resistance behaviors as a novel probe for rapid identification and direct differentiation of “Fasciola hepatica”, “Parascaris equorum” (with and without larvae), “Dicrocoelium dendriticum”, “Taenia multiceps” and “Moniezia expansa” eggs. This claim is attributed to some characteristics such as grave supercapacitance/area, high energy storage/area, large power/egg, huge permittivity, great electrical break-down potential, respectively (Fasciola hepatica: 2158, 0.485, 2.7×10−3, 267, 52.6, Parascaris equorum without larvae: 2825, 0.574, 3.0×10−3, 351, 68.4, Parascaris equorum with larvae: 4519, 0.716, 2.4×10−3, 1.96, 97.6, Dicrocoelium dendriticum: 1581, 0.219, 2.8×10−3, 1.96, 48.8, Moniezia expansa: 714, 0.149, 2.2×10−3, 0.88, 35.2, Taenia multiceps: 3738, 0.619, 4.7×10−3, 4.63, 84.4) and durable capacitance up to at least 15,000 sequential cycles at different scan rates (between 2.0×10−4- 120.0 V s−1) as well as highly differentiated resistance between (400- 600 Ω). These traits are measured by the “Blind Patch-Clamp” methodology, at the Giga ohm sealed condition (6.18 ± 0.12 GΩ cm−1, n=5). Significant detection ranges were detected for each capacitance and resistance with gradient limits as large as at least 880 to 1000 mF and 400 to 600 Ω depending on the type of helminth egg. The effect of water in the structure of helminth eggs, has also been investigated with acceptable reproducibility (RSD 7-10 %, n=5). These intrinsic characteristics would provide novel facilitators for direct helminth egg’s identification in comparison by several methods such as: ELISA, PCR, and microscopic methods.